2003
DOI: 10.1007/bf02695972
|View full text |Cite
|
Sign up to set email alerts
|

The interrelationships among trace element cycling, nutrient loading, and system complexity in estuaries: A mesocosm study

Abstract: Biogeochemical interactions between a suite of trace elements and nutrients were examined in a series of experimental mesocosm experiments to understand how multiple stressors affect estuarine environments and how these effects are modified by the complexity of the system used to examine them. Experimental treatment included additions of nutrients and trace elements separately and combined, along with a gradient in experimental system complexity. Eight mesocosm experiments were carried out from 1996 through 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…Mesocosm studies have confirmed those findings by adding nutrients to stimulate a bloom under controlled conditions. For example, Riedel and Sanders (2003) found that dissolved Zn was depleted in mesocosm studies with Patuxent River water, and Wang et al (2005) showed that phytoplankton accumulated Zn from Hong Kong coastal waters. The contrasting results in our study could be because (1) sampling started too late to capture a Zn drawdown, (2) Zn was rapidly repartitioned from the particulate phase, (3) organic complexation limited Zn bioavailability, or (4) a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesocosm studies have confirmed those findings by adding nutrients to stimulate a bloom under controlled conditions. For example, Riedel and Sanders (2003) found that dissolved Zn was depleted in mesocosm studies with Patuxent River water, and Wang et al (2005) showed that phytoplankton accumulated Zn from Hong Kong coastal waters. The contrasting results in our study could be because (1) sampling started too late to capture a Zn drawdown, (2) Zn was rapidly repartitioned from the particulate phase, (3) organic complexation limited Zn bioavailability, or (4) a combination of these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Along with nutrients, trace metals have also been depleted by blooms in South Bay , the Scheldt estuary (Zwolsman and van Eck 1999), coastal waters (Schoemann et al 1998;Ingri et al 2004), and laboratory mesocosm studies (Beck et al 2002;Riedel and Sanders 2003;Wang et al 2005). In South Bay, the 1994 spring bloom depleted dissolved Cd, Ni, and Zn (but not Cu) from the water .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal ecosystems are becoming increasingly threatened as humans exploit resources and alter habitats (Vituosek et al, 1997;Jackson et al, 2001), and understanding multifactor anthropogenic-induced change is a priority (Riedel and Sanders, 2003;Wiegner et al, 2003). It is therefore important for coastal resource managers, conservationists and ecologists alike to know if the assumptions listed above compromise our understanding of anthropogenic effects.…”
Section: Introductionmentioning
confidence: 99%
“…P is one of backbone elements involving the synthesis of basic structure such as membranes, while Mo is involved in forming active centers of enzymes catalyzing nitrate reduction and nitrogen fixation. In phytoplankton, trace elements commonly interact with each other during biological uptake due to ion competition and/or detoxification (Interlandi, ; Riedel & Sanders, ; Serra, Guasch, Admiraal, Van der Geest, & Van Beusekom, ; Wang & Dei, ). Hall, Healey, and Robinson () observe that P is involved in excluding/eliminating toxic metals from cells in cultures of Chlorella vulgaris .…”
Section: Resultsmentioning
confidence: 99%